If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 25x = 15x + 6 Reorder the terms: 4 + 25x = 6 + 15x Solving 4 + 25x = 6 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 4 + 25x + -15x = 6 + 15x + -15x Combine like terms: 25x + -15x = 10x 4 + 10x = 6 + 15x + -15x Combine like terms: 15x + -15x = 0 4 + 10x = 6 + 0 4 + 10x = 6 Add '-4' to each side of the equation. 4 + -4 + 10x = 6 + -4 Combine like terms: 4 + -4 = 0 0 + 10x = 6 + -4 10x = 6 + -4 Combine like terms: 6 + -4 = 2 10x = 2 Divide each side by '10'. x = 0.2 Simplifying x = 0.2
| x*10+22=x*2+238 | | x*3+131=x*11-5 | | 3x+x+4=10 | | (x^2)(y^2)= | | 5-5n=1-7n | | 8+3-7x-4=-8x+1 | | 7+35x=20x+16 | | 4+25x=15x+16 | | (x^2)(3x^2)= | | -16+2x=-24+9x | | 9b=26+4b | | 3=33x | | 30-2x=10-7x | | 3x+9=-39-5x | | 5+6x=-5+x | | x-2-4x=3+2x | | 2x-4=-9x-25# | | 25x^3+30x+9= | | 10+6x=2(4x-1)+4x | | 6-2k=2-4k | | 3x-x+4=10 | | (-9y^2+7y+7)+(6y^2-5y-9)= | | -1+4x=-4+37x | | sqrt(u-7)=6 | | -4+4x=-4+37x | | 2=-2x+24 | | -m+8m=8m-7 | | 29-5x=11-8x | | sqrt(5w+14+2)=5 | | 7x-20=10x+6 | | 2x+13=-11-4x | | 8+4x=14+x |